Glutamatergic Synapse Dysfunction in Drosophila Neuromuscular Junctions Can Be Rescued by Proteostasis Modulation - Chakravorty, Anushka; Sharma, Ankit; Sheeba, Vasu; Manjithaya, Ravi (Frontiers in Molecular Neuroscience, 2022)
Glutamate is the major excitatory neurotransmitter in the nervous system, and the Drosophila glutamatergic neuromuscular junctions (NMJs) offer a tractable platform to understand excitatory synapse biology both in health and disease. Synaptopathies are neurodegenerative diseases that are associated with synaptic dysfunction and often display compromised proteostasis. One such rare, progressive neurodegenerative condition, Spinocerebellar Ataxia Type 3 (SCA3) or Machado-Joseph Disease (MJD) is characterized by cerebellar ataxia, Parkinsonism, and degeneration of motor neuron synapses. While the polyQ repeat mutant protein ataxin-3 is implicated in MJD, it is unclear how it leads to impaired synaptic function. Here, we show that a Drosophila model of MJD recapitulates characteristics of neurodegenerative disorders marked by motor neuron dysfunction. Expression of 78 polyQ repeats of mutant ataxin-3 protein in Drosophila motor neurons resulted in behavioral defects such as impaired locomotion in both larval and adult stages. Further, defects in eclosion and lifespan were observed in adult flies. Detailed characterization of larval glutamatergic neuromuscular junctions (NMJs) revealed defects in morphological features along with compromised NMJ functioning. Autophagy, one of the key proteostasis pathways, is known to be impaired in case of several synaptopathies. Our study reveals that overexpression of the autophagy-related protein Atg8a rescued behavioral defects. Thus, we present a model for glutamatergic synapse dysfunction that recapitulates synaptic and behavioral deficits and show that it is an amenable system for carrying out genetic and chemical biology screens to identify potential therapeutic targets for synaptopathies.